Creativity of Russian Composer Mikhail Glinka in the Context of National Cultural Traditions - Mikhailovich Kizin, Mikhail (International Journal of Psychosocial Rehabilitation, 2020)
The article analyzes the work of the founder of professional Russian musical culture, composer Mikhail Glinka. Aspects of the influence on the musician’s creativity are examined, based on the experience gained from Western European musical art and culture and traditions of folk and professional Russian culture. The actual influence of Western European music was determined by the creation by Mikhail Glinka of a professional composer and vocal school, which gave a powerful impetus to the development of Russian musical culture, which has become a global phenomenon. The analytical review reveals the universalism of the genius of the composer, manifested in the genre diversity of creativity, which became a guideline for the development of the national opera and the Russian school of singing, symphonic and chamber genres until the end of the 19th century.